Philosophy of change — change in philosophy. Remarks on non-dualizing philosophy of Josef Mitterer - Cyzman, Marzenna (Hybris, 2015)
The present paper is aimed at a short presentation of the non-dualizing way of speaking formulated by Josef Mitterer, the Austrian philosopher. In the first part I focus on metaphilosophical conception of the non-dualism which is assumed as alternative for the dualizing way of speaking (dominating not only in the philosophical discourses but also in ordinary acts of speech). According to the from-object-cognition (which is understood as the option for traditional epistemology directed towards the object), there is no distinction between object and description. Thus, in the non-dualizing way of speaking, one speaks from the object, not about the object. This is impossible to present the object without a rudimentary description. As a consequence, the discourses are directed towards the change, not toward the truth (which is understood as the aim of the dualizng discourses). In the second part of the paper there is a short critique of Mitterer’s analyses, especially the notion of contingency and the notion of description. Assuming that one can formulate any kind of description from the object, Mitterer reaches the idea of anything goes which is unacceptable also from constructivist point of view (S. Fish’s notions, especially institutional nesting, are used in order to provide more acceptable solution: our conceptions are always based on pre-understandings and conventions). The notion of description, the central point of Mitterer’s deliberations, is involved in dualizing and this seems not to be the best way to present the different way of speaking.